Foreign Direct Investment (FDI): A means to address food insecurity? A Nexus Analysis - Voss,Ramón (2016)
Food insecurity is a major problem for humanity. Especially in developing countries, the proportion of people who go to bed hungry is substantial. A basic reason, among other factors, is the dominant poverty in those regions. Therefore, many development organizations consider Foreign Direct Investment (FDI) as a means, which has the potential to regulate these inequalities in developing countries. FDI in developing countries should be able to close financial gaps and thus generate economic growth. Economic growth in developing countries is seen as a key to reduce national poverty and achieve food security. Various development organizations, researchers and scientists analyze the impact of FDI on the target economies in order to evaluate whether FDI can induce the desired positive effects. In this thesis the theoretical framework of Rein and Schön (1996) is used to examine secondary literature on whether FDI can contribute to food security in food insecure developing economies. The literature provides theoretical and empirical examples of how FDI affects the target economy. These results, however, are not unanimous and lead to different views on FDI in developing economies. On the one hand it is argued and demonstrated that FDI in developing countries can contribute to economic growth, which is seen as a prerequisite for food security. These studies and reports attest FDI as having a positive influence on the target economy. Beyond just financial capital, FDI creates new jobs, enhances human capital, introduces new technologies and contributes to increased production in the target economy which result in economic growth and should enable food insecure developing countries to become food secure. Other researchers come to different conclusions. According to their theories and findings, FDI does not necessarily result in positive effects for the developing target economy. In their perception, foreign investors rather take advantage of developing countries among others by stealing land from destitute people, paying low wages or selling produced goods on the global market with low revenue streams for the developing economy. They promulgate that economic growth and food security in food insecure developing countries cannot be reached through FDI. In some cases, it evens seems that FDI exacerbates food insecurity.
Keywords: FDI; food security; food insecurity; economic growth; poverty reduction.